A tributação ambiental na reforma tributária - Iovanovich, Zuleica Ap (2025)
This paper investigates the effects of the promulgation of Constitutional Amendment 132/2023, which elevated the principle of environmental protection to the category of a constitutional tax principle. The analysis goes beyond the normative aspect, seeking to evaluate the real capacity of EC 132/2023 to generate tangible changes. To do so, it is crucial to understand how this alteration— which aligns with the global trend of using taxation as a driver for sustainability—can translate into effective fiscal policies that encourage more responsible practices, minimizing negative environmental impacts